Neonatal lethality of neural crest cell‐specific Rest knockout mice is associated with gastrointestinal distension caused by aberrations of myenteric plexus. (18th August 2014) - Aoki, Hitomi; Hara, Akira; Oomori, Yoshiyuki; Shimizu, Yasutake; Yamada, Yasuhiro; Kunisada, Takahiro
<x xml:space="preserve">Abstract</x> RE1‐silencing transcription factor (REST), also known as NRSF (neuron‐restrictive silencer factor), is a well‐known transcriptional repressor of neural genes. Rest null mice have embryonic lethality which prevents further investigations of the functions of the Rest gene in vivo. We studied neonatal but not embryonic lethality that was characterized by gastrointestinal tract dilation in the neural crest cell (NCC)‐specific Rest conditional knockout (CKO) mice. While no histological abnormalities except the thinning of the digestive tract as a consequence of the gas accumulation were found in the digestive tract of the mutant mice, they do not have proper gastric retention after oral dye administration and the reduction of acetylcholinesterase (AChE) activity in NCC‐derived myenteric plexus in the stomach was detected. High CO2 concentration in the dilated digestive tract of the Rest CKO mice indicates a failure of gut function by underdeveloped cholinergic transmission in the enteric nervous system. The observed gastrointestinal distension phenotype provides a model for understanding the genetic and molecular basis of NCC defects in humans.